Budaya Lokal sebagai Fondasi Pendidikan Inklusif pada PAUD dan Sekolah Dasar - Kamilah, Nanda Isrina; Muna, Lailil; Rahma, Fatikh Inayahtur (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2026)
This study aims to explore how eco-theology can be integrated into Natural and Social Sciences (IPAS) learning as a framework for fostering primary school students' understanding of the relationship between humans and the environment. Using a library research approach, this study reviewed various literature on environmental education, ecotheology, and science learning to identify patterns, conceptual trends, and the potential for integrating spiritual values into IPAS. The results of the study indicate that ecological relationships, context-based learning experiences, and the instilling of moral-spiritual values are important elements in effective environmental education. These findings were then analysed using Bronfenbrenner's Ecological Systems Theory and eco-theological principles to formulate an integrative model that connects ecological experiences across various student development systems with key eco-theological values, such as ecological monotheism, khilafah, amanah, and mīzān. The model emphasises that integrating ecotheology can shift IPAS learning from a purely cognitive focus to a more holistic, transformative learning process rich in ethical and spiritual values. This research, therefore, contributes a conceptual integrative framework and design propositions for ecotheology-based IPAS learning, which may serve as a theoretical foundation for further empirical validation and model feasibility testing.